Stylistic Structures of the Husseini Revolution Illustrations in the Paintings of Muslim Painters - Hadi Hassan, Hassan; Kadhim Ali , Abdul (Journal of College of Education, 2019)
Appearing in front of the revolution of Hussein, peace be upon him and trying to read it stylistically, according to the expressive artistic perspective through which the various Muslim artists dealt with that event and inspired them in their plastic data, carries a plaudits for the epic values, dramatic scenes, and moral structures that extrapolate the meanings of human meanings by their standards. Engaging with the conscious anthropological system, which is suitable to be a plastic plate carrying a high intellectual content and a distinct formative construction at all times and places. Moreover, the attempt to embody the personalities and events associated with this incident varies even in the regional and geographical aspect related to the display of these drawings. Differences in the stylistic aspect of the productions of artists in different parts of the Islamic world appeared, depending on the various factors and stressing differences, which together formed axes that gave different artistic dyes. In her speeches and formative patterns, the current research sheds light on those methods, and the technical structural treatments used to show their different formal formulations, and may be of four chapters, the first chapter is devoted to the problem of research and The second chapter, whose theoretical framework consisted of three topics: (style and stylistic means of systematic expression) and (technical methods of Islamic painting and spirit of expression). And (stylistic elements of the depictions of the Husseinian revolution in the paintings of Muslim painters), while the third chapter concerned with research procedures, which included a research community consisting of selected models of the work of Muslim artists dedicated to the glorification of the Husseini revolution, which appeared in a number of Islamic capitals, and was selected (3) paintings from Yes Muslim artists considered the subject as an intentional choice that represented the research sample. It was analyzed according to the descriptive and analytical method. The fourth chapter included the most important findings and conclusions of the research..